Muhammad Abduh Dan Ijtihadnya Dalam Bidang Pendidikan - Suhaimi Suhaimi (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2015)
Since the arrival of Napoleon Bonaparte to Egypt in the late 19th century AD, the Islamic world can be said to have been aware of the lag in many areas including in the field of education. Therefore, among the scholars at the same time Muslim intellectuals in the Islamic world when it started thinking to bounce back and catch up with the Islamic world experienced such a variety of ways that may be carried out according to the conditions at that time. Among them was Sheikh Muhammad Abduh. In the course of his life, Abduh has done ijtihad and renewal through the various ideas put forward ideas or even gets serious challenges from various parties, including the scholars of al-Azhar itself. But all of that does not make him despair and retreat, so that his ideas had a great influence for the next generation. Abduh brilliant ideas include the fields of education, legal, social, administrative, political and others. This article only focuses his discussion on his thoughts about education which would still be relevant to observe in order to be an afterthought for students of education in this country. Abduh's ideas include the following educational objectives, curriculum, methods and the importance of education for women. ABSTRAK Sejak kedatangan Napoleon Bonaparte ke Mesir pada akhir abad ke 19 Masehi, dunia Islam dapat dikatakan telah menyadari akan ketertinggalan di berbagai bidang termasuk di bidang pendidikan. Karena itu, di antara ulama sekaligus intelektual muslim di dunia Islam saat itu mulai berfikir untuk bangkit kembali serta mengejar ketertinggalan yang dialami dunia Islam tersebut dengan berbagai cara yang mungkin dilakukan sesuai kondisi saat itu. Di antara mereka adalah Syeikh Muhammad Abduh. Dalam perjalanan hidupnya, Abduh telah melakukan ijtihad dan pem-baharuannya melalui berbagai ide atau gagasan yang dikemukakannya sekalipun mendapat tantangan yang berat dari berbagai pihak termasuk pihak ulama al-Azhar sendiri. Akan tetapi semua itu tidak membuatnya berputus asa dan mundur, sehingga ide-idenya mempunyai pengaruh yang besar bagi generasi berikutnya. Ide-ide cemerlang Abduh meliputi bidang-bidang pendidikan, hukum, sosial, administrasi, politik dan lain-lain. Tulisan ini hanya memfokuskan bahasannya di seputar pemikirannya di bidang pendidikan yang kiranya masih relevan untuk dicermati guna menjadi renungan bagi para pemerhati pendidikan di negeri ini. Ide-ide pendidikan Abduh antara lain meliputi tujuan, kurikulum, metode dan pentingnya pendidikan bagi kaum wanita. Kata Kunci: Abduh, Ide-ide pendidikan